Impact of Single Bout of Physical Exercise on Adolescents’ Strength and Balance Abilities (Baltic Journal of Sport and Health Sciences, 2015)
Background. There is evidence of physical exercise effect on the adolescents’ balance and strength; however it is not known how aforementioned variables respond to physical exercise with different loads and intensities. Therefore, the aim of the study was to assess the impact of single bout of physical exercise of different intensity on adolescents’ body balance and muscular strength.Methods. Thirty healthy, physically active 11–13-year-old adolescents were randomly allocated to one of the two groups. Both groups performed single bout of physical exercise of high- or low-intensity climbing up and down-stairs. Postural sway and maximum voluntary contractions (MVC) were assessed before and after physical exercise. Results. No statistically significant impact of low or high intensity exercise was found at adolescents’ MVC. High intensity exercise influenced bigger postural sway with eyes closed compared to eyes open ( p < .05). After high-intensity exercise there was a significantly greater postural sway with eyes closed than with eyes open (p < .05). Conclusions. High and low intensity physical exercise had no impact on the adolescents’ maximum voluntary contraction, whereas high intensity exercise deteriorated body balance with eyes closed.Keywords:  adolescence, physical exercise, MVC, balance